NURSES’ ACTIVITY IN THE PRIMARY PREVENTION OF DIABETES - Shodiyabonu Erkaboyeva (World Scientific Research Journal, 2025)
Abstract: this article describes the causes of diabetes and the effective use of nurses’ activities as a primary preventive measure in its prevention, gaining an understanding of the disease, etc. The purpose of this thesis is to study the importance of the activities of nurses in the primary prevention of diabetes and to analyze their impact on patients. The results of this study help to strengthen the role of nurses in the health system and give them an important place in the prevention of diabetes.